Training in Quran Literacy and Tafsir for the Younger Generation in Facing the Digital Disinformation Tide: Penelitian - Andri Nirwana An; Mahmudulhassan; Muthoifin; Waston; Sajiwo Tri Prakoso (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to improve the Quranic and Tafsir literacy of young people so they can counter digital disinformation, particularly on religious issues. Based on a community service learning model (KKN) that combines experience and community involvement, this research equips young people with critical thinking skills regarding online information and the application of Quranic principles in their lives. The training program for 15–25 year olds includes Quranic analysis, Tafsir practice, and discussions on identifying disinformation, complemented by simulations and reflective exercises. Results show increased knowledge, critical awareness, and the ability of participants to recognize and counter religious disinformation. This research bridges religious education and digital literacy by offering effective tools for young people to navigate the digital era without abandoning religious values. This study is unique because it integrates Quranic and Tafsir literacy with community service, thus presenting a new approach to empowering young people to face the challenges of modern education and misinformation..